Immature hard ticks infected with Rickettsia amblyommatis on breeding birds from Pantanal - Fecchio, Alan (2023)
Immature hard ticks from the genus Amblyomma feed on blood from a wide range of Neotropical avian hosts. They serve as vectors for pathogens of medical and veterinary importance, such as Rickettsia agents of the spotted fever group (SFG). Hence, determining ecological factors that increase encounter rates between immature ticks and their avian hosts may contribute to the understanding of tick-borne diseases transmission. Here, we used 720 individual birds from 96 species surveyed in the Brazilian Pantanal to test whether host breeding season influenced tick infestation probabilities. Additionally, collected ticks were screened for Rickettsia agents to describe new avian-tick-bacteria associations. Our models revealed that the probability of an individual bird being infested with immature ticks was similar during the breeding and pre-breeding season, but higher loads of immature tick stages were found during the breeding season. Host sex did not predict infestation probability, but Rickettsia agents recovered from ticks were more prevalent during the pre-breeding season. The new records of host usage by larvae and nymphs of Amblyomma in Pantanal and the growing body of tick surveys in Neotropical avian communities, suggest that immature ticks may benefit from avian blood sources during their annual cycle. The low number of infected ticks with Rickettsia agents on Pantanal birds suggest that this vertebrate group are likely not acting as reservoirs for these microorganisms. However, long-term surveys at the same site are imperative to determine which tick species are acting as reservoirs for Rickettsia agents in Pantanal and determine whether birds are playing a role in dispersing ticks and tick-borne pathogens.